Intranet design annual 2009 : the year's 10 best intranets - Pernice, Kara (Nielson Norman Group, 2009)
"This report from the Nielsen Norman Group reviews the designs and usability of ten intranets that were chosen from a much larger number of nominated designs. The report is richly illustrated with 241 full-color screenshots, giving readers the unique opportunity to see good intranet designs that are usually hidden behind a firewall. These intranets represent big companies with large amounts of documents and mission-critical applications such as sales force support. But most of the lessons from these winning designs apply to smaller companies as well. The bulk of the report consists of detailed case studies of each of the ten winning intranet designs, including discussions of the main problems they faced, how these problems were overcome in the redesign process, and how the new design compared with the previous design"--Resource description page.